2022
DOI: 10.2147/ijgm.s360582
|View full text |Cite
|
Sign up to set email alerts
|

Is Travel Time Associated with Health Service Utilization in Northwest China? Evidence from Shaanxi Province

Abstract: Purpose Northwest China has a large area, low population density, and few health resources, which makes the utilization of health resources in this region difficult. The objective of this study was to assess utilization of health services and its association with travel time in Shaanxi Province. Patients and Methods Data were obtained from the fifth Household Health Service Survey of Shaanxi Province conducted in 2013. Binary logistic regression was used to assess the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
1
Order By: Relevance
“…Poor physical access to health facilities was identified as a key contributor to reduced uptake of preventive health services [25]. The current finding on time to health facility doesn't conform to a study done in China which found no correlation between travel time, utilization and uptake among rural residents in Shaanxi Province [26] owed to different contexts of pastoral context in the current study. Very few studies have been conducted in pastoral settings and perhaps limited data to support these results but confirms the need for future investigations using other multilevel approaches [27].…”
Section: Discussioncontrasting
confidence: 92%
“…Poor physical access to health facilities was identified as a key contributor to reduced uptake of preventive health services [25]. The current finding on time to health facility doesn't conform to a study done in China which found no correlation between travel time, utilization and uptake among rural residents in Shaanxi Province [26] owed to different contexts of pastoral context in the current study. Very few studies have been conducted in pastoral settings and perhaps limited data to support these results but confirms the need for future investigations using other multilevel approaches [27].…”
Section: Discussioncontrasting
confidence: 92%